(untitled) (Latakia University Journal - Arts and Humanities Sciences Series, 2020)
The door out one of the doors that Tjazptha grammar books and drainage, and almost devoid writers of these books of Study or Investigation in Gay out, agree to mention issues and words anomalies, and vary degree is large in the reasons and illnesses, to receive then described as came Unlike measurement, not increased Alnhoyen modern studies of the transport of the books of the ancients on the difference in the degree of give-and-supply and tab. This research aims to extrapolate Gay out, and identify Hdhuzha after returning to the standard weights developed by scientists or classified as enemy anomaly - in terms of the nature of homosexuality - into sects and divisions, and the statement of the reasons that led to their rule by homosexuality, with the stand to explain the scientists of the causes and ills abnormalities words and formulas out, then inventory anomalous terms that do not walk according to the rules of miniaturization and linked in the rules and relations gathered them and distinguish them from what else. يعدّ باب التّصغير من الأبواب التي تجاذبتها كتب النّحو والصّرف ، ولا يكاد يخلو كتاب من هذه الكتب من مبحث أو مباحث في شواذّ التّصغير، تتفق في ذكر المسائل والألفاظ الشّاذة، وتختلف بدرجة غير كبيرة في ذكر الأسباب والعلل ، لتلقي بعد ذلك في وصفها بأنّها جاءت على خلاف القياس ، ولم تزد دراسات المحدثين من النّحويين على النّقل من كتب القدماء على اختلاف في درجة الأخذ والعرض والتّبويب . ويهدف هذا البحث إلى استقراء شواذ التّصغير ، وتحديد شذوذها بعد الرّجوع إلى الأوزان القياسيّة التي وضعها العلماء أو تصنيف ما عدّوه شاذّاً – من حيث طبيعة الشّذوذ – إلى طوائف وأقسام ، وبيان الأسباب التي أدّت إلى حكمهم عليها بالشّذوذ ، مع الوقوف على تعليل العلماء لأسباب وعلل شذوذ ألفاظ وصيغ التّصغير ، ثمّ حصر الألفاظ الشّاذّة التي لا تسير وفق قواعد التّصغير وربطها في قواعد وعلاقات تجمع بينها وتميّزها عمّا عداها .